The Life of Seafarers in the Digital Age: An Analysis of the Philosophy of Ethics and Morality in the Use of Technology - Sumartono, Eddy (Arbain Publishing, 2024)
This research explores the dynamics of seafarers' lives in the face of digital transformation with a focus on the ethical and moral aspects of the use of technology. Through a qualitative approach with phenomenological design, the study involved 15 seafarers from various levels of position. Data collection was carried out through in-depth interviews, participatory observations, and document analysis. The results reveal that digital transformation has fundamentally changed the way seafarers work and interact socially, with varying rates of technology adoption on various aspects of ship operations. Data privacy and moral responsibility are top concerns, while social interaction patterns show significant declines in direct communication and team cohesion. L’écart entre l’urgence de développer des compétences numériques et la disponibilité de programmes de formation adéquats est un défi majeur. Cette recherche apporte une contribution importante à la compréhension des implications éthiques et morales de la numérisation maritime, et souligne la nécessité d’une approche plus holistique du développement des compétences numériques des gens de mer, qui tienne compte des aspects techniques, éthiques et sociaux.